Case Report: Lymphoepithelial Carcinoma of the Parotid Gland with EBV Association - Subramaniam , S Darmma; Mansor, Masaany (IIUM Medical Journal Malaysia, 2022)
Primary Lymphoepithelial Carcinoma (LEC) of the salivary gland is a rarely encountered malignant tumour by Otorhinolaryngology surgeons especially in Malaysia. It accounts for an estimated 0.4% of all malignant tumours of head and neck with a racial predilection towards Eskimos, people of Southern Costal of China and Japanese. Histologically it exhibits a poorly differentiated neoplasm and a strong association with Epstein-Barr virus that could be similar to an undifferentiated nasopharyngeal carcinoma (NPC). The parotid gland is the most common location a Primary LEC of the salivary gland develops, with patients mostly presenting with a painless parotid swelling and cervical lymphadenopathy. Herein, the authors report a rare case of Primary LEC of the parotid in an unfortunate Malay female. In this case report we further highlight the pathological and radiological features including management of Primary LEC of the parotid as this tumour should be considered in all patients presenting with a painless parotid mass to an Otorhinolaryngology clinic.